Bibliometric analysis of peer-reviewed literature on climate change and human health with an emphasis on infectious diseases - Waleed M. Sweileh (BMC, 2020)
Abstract Background Assessing research activity is important for planning future protective and adaptive policies. The objective of the current study was to assess research activity on climate change and health with an emphasis on infectious diseases. Method A bibliometric method was applied using SciVerse Scopus. Documents on climate change and human health were called "health-related literature" while documents on climate change and infectious diseases were called "infection-related literature". The study period was from 1980 to 2019. Results The search query found 4247 documents in the health-related literature and 1207 in the infection-related literature. The growth of publications showed a steep increase after 2007. There were four research themes in the health-related literature: (1) climate change and infectious diseases; (2) climate change, public health and food security; (3) heat waves, mortality, and non-communicable diseases; and (4) climate change, air pollution, allergy, and respiratory health. The most frequently encountered pathogens/infectious diseases in the infection-related literature were malaria and dengue. Documents in infection-related literature had a higher h-index than documents in the health-related literature. The top-cited documents in the health-related literature focused on food security, public health, and infectious diseases while those in infection-related literature focused on water-, vector-, and mosquito-borne diseases. The European region had the highest contribution in health-related literature (n = 1626; 38.3%) and infection-related literature (n = 497; 41.2%). The USA led with 1235 (29.1%) documents in health-related literature and 365 (30.2%) documents in infection-related literature. The Australian National University ranked first in the health-related literature while the London School of Hygiene & Tropical Medicine ranked first in the infection-related literature. International research collaboration was inadequate. Documents published in the Environmental Health Perspectives journal received the highest citations per document. A total of 1416 (33.3%) documents in the health-related literature were funded while 419 (34.7%) documents in the infection-related literature were funded. Conclusion Research on climate change and human health is on the rise with research on infection-related issues making a good share. International research collaboration should be funded and supported. Future research needs to focus on the impact of climate change on psychosocial, mental, innovations, policies, and preparedness of health systems.